Our Mythical Childhood... the Classics and Literature for Children and Young Adults - Marciniak, Katarzyna (Metaforms Ser, 2016)
Our Mythical Childhood…: The Classics and Literature for Children and Young Adults -- Copyright -- Contents -- List of Figures -- Notes on Contributors -- What Is a Classic… for Children and Young Adults? -- PART 1: In Search of Our Roots: Classical References as a Shaper of Young Readers' Identity -- 1: From Aesop to Asterix Latinus: A Survey of Latin Books for Children -- 2: Childhood Rhetorical Exercises of the Victor of Vienna -- 3: The Aftermath of Myth through the Lens of Walter Benjamin: Hermes in J.M. Barrie's Peter Pan in Kensington Gardens and in Astrid Lindgren's Karlson on the Roof -- 4: A Latin Lesson for Bad Boys, or: Kipling's Tale of the Enchanted Bird -- 5: Laura Orvieto and the Classical Heritage in Italy before the Second World War -- 6: Saul Tchernichowsky's Mythical Childhood: Homeric Allusions in the Idyll "Elka's Wedding" -- 7: Jadwiga Żylińska's Fabulous Antiquity -- 8: A Child among the Ruins: Some Thoughts on Contemporary Modern Greek Literature for Children -- 9: The Reception of Classical Antiquity in Polish Lexicography for Children and Young Adults -- PART 2: The Aesop Complex: The Transformations of Fables in Response to Regional Challenges -- 10: Our Fabled Childhood: Reflections on the Unsuitability of Aesop to Children -- 11: A Gloss on Perspectives for the Study of African Literature versus Greek and Oriental Traditions -- 12: Aesop's Fables in Japanese Literature for Children: Classical Antiquity and Japan -- 13: Vitalis the Fox: Remarks on the Early Reading Experience of a Future Historian of Antiquity in Poland (1950s-1960s) -- 14: Aemulating Aesopus: Slovenian Fables and Fablers between Tradition and Innovation -- PART 3: Daring the Darkness: Classical Antiquity as a Filter for Critical Experiences -- 15: Armies of Children: War and Peace, Ancient History and Myth in Children's Books after World War One.